2012
DOI: 10.1002/rcm.6409
|View full text |Cite
|
Sign up to set email alerts
|

Identification and separation of protein, contaminant and substrate peaks using gentle‐secondary ion mass spectrometry and the g‐ogram

Abstract: The g-ogram method effectively separates out mass peaks relating to the substrate, contamination and protein without any a priori information or subjective decisions about which peaks to include in the analysis (so called 'peak picking'). This is a great help to analysts. We find two possible peaks from plural amino acids but no evidence of pluralities is found for peaks above 240 Da that are generated from when using Bi or Mn primary ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Obviously, on mixtures containing molecules with strongly different fragmentation behavior, the G‐SIMS method may not be enough to identify or distinguish all molecules present, and an approach in which the g factor is varied (i.e. g ‐ogram) may be more adequate. Nevertheless, we have shown that G‐SIMS allows to identify one component, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, on mixtures containing molecules with strongly different fragmentation behavior, the G‐SIMS method may not be enough to identify or distinguish all molecules present, and an approach in which the g factor is varied (i.e. g ‐ogram) may be more adequate. Nevertheless, we have shown that G‐SIMS allows to identify one component, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Although ToF‐SIMS is capable for obtaining surface chemical information, ToF‐SIMS data is so intricate that it is difficult to find out appropriate secondary ions for chemical imaging or those only specific to Aβ. Therefore, multivariate analysis such as principal component analysis (PCA) and spectrum analysis such as G‐SIMS and g‐ogram have been applied to ToF‐SIMS data in the previous study . In this study, PCA results were compared in detail in order to find the surface differences of Aβ regarding amino acid residues depending on the lipid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if it worked well, it is possible to extract the useful information which could not be understood without using it. Gentle‐SIMS (G‐SIMS) and g‐ogram were developed by National Physical Laboratory to interpret Static‐SIMS spectra more effectively. The information about the original chemical structure of a certain secondary ion and the relationships between fragment ions can be obtained by using those methods.…”
Section: Introductionmentioning
confidence: 99%